Reading and Transcription of a Tetra-Stranded Genetic Polymer : Decoding Channels, Controlled Ambiguities, and the Formal Definition of the Q-Code - Barack Ndenga (Publisher, 2025)
Transcription is commonly defined as template-directed RNA synthesis mediated by a polymerase. However, this definition is historically contingent on duplex DNA and is not a logical necessity for heredity. In this work, I develop a general framework for reading and transcription in Q-DNA, defined as a canonical tetra-stranded hereditary polymer, without assuming the existence of a classical RNA polymerase. I introduce the notion of decoding channels, formalize local and topological readout mechanisms, and analyze the emergence and resolution of controlled ambiguities inherent to multi-strand encoding. This framework leads to a precise definition of the Q-code and establishes explicit constraints on any physical or enzymatic system capable of reading tetra-stranded genetic information.
Transcription is commonly defined as template-directed RNA synthesis mediated by a polymerase. However, this definition is historically contingent on duplex DNA and does not constitute a general definition of genome reading. For alternative hereditary systems, the central problem is not how to transcribe DNA-like sequences, but how stored genetic information is decoded into functional outputs. In this work, I develop a general framework for reading and transcription in Q-DNA, defined as a canonical tetra-stranded hereditary polymer, without assuming the existence of a standard RNA polymerase. I introduce the concept of decoding channels, representing distinct physical mechanisms by which information can be extracted from a multi-stranded genome, including sequence-based projection, local window decoding, and topological or geometric recognition. I explicitly analyze the emergence of decoding ambiguities inherent to multi-strand encoding and show that such ambiguities are not failure modes but controllable design parameters. Strategies for ambiguity resolution—including consensus across channels, temporal integration, and structural filtering—are formalized within an information-theoretic framework. This leads to a precise definition of the Q-code, understood not as a simple alphabet but as a set of admissible mappings between local tetra-stranded configurations and output symbols under structural and readout constraints. Finally, I derive falsifiable predictions regarding window-size dependence, topological sensitivity, and the coexistence of multiple inequivalent readout channels. By decoupling genome reading from specific biochemical implementations, this work establishes decoding as a decisive and testable criterion for evaluating Q-DNA as a viable hereditary system and situates tetra-stranded heredity within a rigorous framework of theoretical biology, synthetic genetics, and information theory.